Different genetic strategies to generate high amylose starch mutants by engineering the starch biosynthetic pathways. (1st July 2022) - Zhong, Yuyue; Qu, Jian Zhou; Liu, Xingxun; Ding, Li; Liu, Ying; Bertoft, Eric; Petersen, Bent L.; Hamaker, Bruce R.; Hebelstrup, Kim Henrik; Blennow, Andreas
Abstract: This review systematically documents the major different strategies of generating high-amylose (HAS) starch mutants aiming at providing high resistant starch, by engineering the starch biosynthesis metabolic pathways. We identify three main strategies based on a new representation of the starch structure: 'the building block backbone model': i) suppression of starch synthases for reduction of amylopectin (AP) side-chains; ii) suppression of starch branching enzymes (SBEs) for production of AM-like materials; and iii) suppression of debranching enzymes to restrain the transformation from over-branched pre-AP to more ordered AP. From a biosynthetic perspective, AM generated through the second strategy can be classified into two types: i) normal AM synthesized mainly by regular expression of granule-bound starch synthases, and ii) modified linear AP chains (AM-like material) synthesized by starch synthases due to the suppression of starch branching enzymes. The application of new breeding technologies, especially CRISPR, in the breeding of HAS crops is also reviewed. Graphical abstract: Unlabelled Image